The Integration of the Highway and Landform - (:unkn) unknown (My University, 1988)
This research stresses the artistic potential of the roadway through the introduction of formal design elements. Using landscape, median, spanning, roadway and enclosure within highway planning and design, the design professional can introduce a new vocabulary to the process of highway construction. Presents a range of design possibilities which, when combined with the technological requirements of a highway system, can lead to a unique and identifiable "design aesthetic." Supported by a grant from the National Endowment for the Arts.